(untitled) (Semiárida, 2020)
Three species and two varieties of Rhynchosia (R. divesifolia Mich. Var. diversifolia, R. diversifolia var. prostrata Burk., R. edulis Gris., R. senna Gil. ex Hook. et Arn. Var. senna y R. senna var. texana (Torr. et Gray) M.C. Johnston, grow naturally in the south of the Province of Cordoba. This paper provides an illustration, description, ecological data, and geographical distribution of each taxon. A key is included term their Identification.